Photosynthetic Characteristics and Chloroplast Ultrastructure of Summer Maize Response to Different Nitrogen Supplies - Liu, Zheng; Gao, Jia; Gao, Fei; Liu, Peng; Zhao, Bin; Zhang, Jiwang (Frontiers in Plant Science, 2018)
Maize (Zea mays L.) is the important crop over the world. Nitrogen (N) as necessary element affects photosynthetic characteristics and grain yield of summer maize. In this study, N0 (0 kg N ha-1), N1 (129 kg N ha-1), N2 (185 kg N ha-1), and N3 (300 kg N ha-1) was conducted using hybrid ‘ZhengDan958’ at Dawenkou research field (36°11'N, 117°06'E, 178 m altitude) in the North China Plain to explore the effects of N rate on photosynthetic characteristics and chloroplast ultrastructure. Gas exchange parameters, chlorophyll fluorescence parameters, leaf area index (LAI), chlorophyll SPAD value, chloroplast ultrastructure, dry matter weight and grain yield were measured. At physiological maturity stage, dry matter weight and grain yield of N2 increased by 33-52% (P≤0.05) and 6-32% (P≤0.05), respectively, compared with other treatments. During the growing from silking (R1) to milk (R3) stage, LAI of N0 and N1 were 35-38% (P≤0.05) and 9-23% (P≤0.05) less than that of N2, respectively. Chlorophyll SPAD value of N0 and N1 were 13-22% (P≤0.05) and 5-11% (P≤0.05) lower than that of N2. There was no significant difference in LAI and chlorophyll SPAD value between N2 and N3 during the period from R1 to R3 (P˃0.05). The net photosynthetic rate (Pn), maximal quantum efficiency of PSII (Fv/Fm) and quantum efficiency of PSII (ΦPSII) were higher with the increase of N rate up to N2 (P≤0.05), and those of N3 were significantly less than N2 (P≤0.05). In compared with N2, the chloroplast configuration of N0 and N1 became elliptical, almost circular or irregular. The membrane of chloroplast and thylakoid resolved with growing stage, and the number of chloroplast per cell and lamellae per grana decreased under N0 and N1 treatment (P≤0.05). Under N0 and N1 treatments, summer maize had more negative photosynthetic characteristics. The more number of osmium granule and vesicle and the larger gap between lamellae were shown in N3. Therefore, N2 treatment, 185 kg N ha-1, is the appropriate application rate for grain yield, photosynthesis and chloroplast ultrastructure.